DEPENDENCE OF THE BEANDNA TERMODINAMIC PARAMETERS FROM THE $^{137}$Cs AND $^{40}$K CONTENTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
Radiation monitoring of the beans (Vida faba) selected from six areas of Armenian NPP location regions was carried out. The choice of regions was determined by direction of die wind rose in this region. For control we used the bean from region 60 km away from NPP. We studied parameters of quality and growth physiology of the bean seeds. DNA has been isolated from the sprouts. The melting profiles, enthalpy of helix-coil transition, spectra of circular dichroism of these isolated DNAs were investigated. The results of researches allow to conclude, that small changes on l37Cs and 40K contents in the beans samples from various regions do not influence on DNA structure.
Keywords: beans; Armenian NPP; parameters of quality; growth physiology